Hydrodynamics of a three-phase external-loop airlift bioreactor - Freitas, Carla Maria Duarte de (2000)
The effect of the distributing plate orifice diameter, airflow rate, solids loading and solids density on the hydrodynamic characteristics - gas holdup, circulation time and liquid velocity - of a three-phase external-loop airlift reactor was characterized. It was observed that the gas distributor has a small effect on riser gas holdup, circulation time and downcomer liquid velocity. On the contrary, the airflow rate, solids loading and solids density significantly affect the hydrodynamic characteristics of the external-loop airlift reactor. A previously described model was used to estimate simultaneously both the riser gas holdup and the downcomer linear liquid velocity. The model simulated with high-accuracy experimental data obtained with three different distributing plate orifice diameters, two solids density and solids loading up to 30% (v/v).